Molecular signatures of neural connectivity in the olfactory cortex - Assunta Diodato (Nature Portfolio, 2016)
The piriform cortex projects to multiple brain regions involved in diverse aspects of olfactory behavior but information about the organization of these outputs is lacking. Here the authors show that piriform neurons exhibit layer specific gene expression patterns that also define distinct projection targets.